PROSPEK PERKEMBANGAN INDUSTRI LILIN LEBAH DI KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Veronika, Nia; Harahap, Azwar; Setiawan, Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The topic for the essay writing on how the development trend of the future production of beeswax. This study aims to determine the development trend of production of beeswax in the District of Gunung Sahilan Kampar regency in 2017 until 2021. The data used in this study are primary data such as industrial production data beeswax the period 2010 to 2016, where these data are Data normality. Furthermore, the data is processed and analyzed using Least Square method (Least Square Method). The results of this study indicate that the quantity of production of the last 7 years of industry beeswax in District Gunung Sahilan Kampar Regency fluctuate from year to year. From the linear trend line equation is Y '= 2035.71 - 398,21X, it is known that the trend in industrial production beeswax tends to decrease, while forecasting trends in 2017 until 2021 also decreased. This suggests that the development trend of industrial production beeswax experienced negative movements.Keywords: Production, Beeswax Industry, Least Squares Method.